PENGARUH MADRASAH KUFAH DALAM KITAB NAHWU YANG DIAJARKAN DI INDONESIA - Halimatus Sa'diyah; Maman Abdurahman; Asep Sopian (Hijai - Journal on Arabic Language and Literature, 2021)
تناقش هذه الدراسة مدرسة الكوفة التي كان لها تأثير كبير على تطور اللغة ، خاصة في استخدام المصطلحات في كتاب النحو. استخدمت هذه الدراسة منهج الدراسة الأدبية والمنهج النوعي لمعرفة تأثير مدرسة الكوفة على الكتاب الذي يستخدمه الطلاب الإندونيسيون لتعلم اللغة العربية وهو كتاب الجرمية. وأظهرت نتائج الدراسة أن ابن عجورم مؤلف الكتاب من أتباع مدرسة الكوفة ، ويدل على ذلك العديد من المصطلحات المستخدمة في مدرسة الكوفة والتي تستخدم أيضا في كتاب الجرمية على النحو التالي: (1) استخدام مصطلح الخفض للإشارة إلى اعراب اسم الذي يتميز بكسره وليس جر (2) استخدام المصطلح "المفعول الذي لم يسم فاعله لمصطلح الفاعل في الفعل المبني للمجهول ، وليس لمصطلح نائب الفاعل. (3) استخدام مصطلح كيف ما هو جزء من الأفعال الجوازم أو عامل الذي يمكن أن يضع فعل مضارع في مرتبة المجزوم كما يعتقد علماء الكوفة. (4) وعلامة الاسم هي إدراج الألف واللام كما يعتقد علماء الكوفة ، أما عند علماء البصرة فإن هذا هو حكم الألف واللام. لا السيفة. (6) استخدام الأسماء الخامسة وهي أبوك، أخوك، حموك، فوك، ذو مال، بينما استخدم علماء البصرة الأسماء الستة بإضافة هنوك.]This study discusses the Kufah Madrasah which has had a lot of influence on the development of Nahwu, especially on the use of terms in the Arabic grammatical book. This study used a literary study method and a qualitative approach to find out the influence of the Kufah madrasah on the book used by Indonesian students to learn Arabic, namely the al-Jurumiyah book. The results of the study show that Ibn Ajurrum, the author of the book, is a follower of the Kufa madrasah, this is indicated by the many terms used in the kufah madrasah which are also used in the al-Jurumiyah book as follows, (1) the use of the term al-khafd for i'rab isim which marked by kasroh, not the term jarr; (2) the use of the term al-maf'ul al-ladhi lam yusamma fa'iluh for the term subject in the passive verb, not the term na'ib al-fa'il; (3) the use of the term kayfama is part of al-af'al al-jawazim or of amil (particle) which can put fi'il mudari 'into the majzum position, as believed by kufah scholars; (4) the sign of a noun is the inclusion of alif and lam as believed by Kufah scholars, whereas according to the scholars of Basrah, this is the rule of alif and lam (5) the use of the term an-na'at, not al-sifah; (6) the use of al-asma al-khamsah, namely abuka, akhuka, hamuka, fuka, dhu mal, while Basrah scholars used al-asma al-siita by adding hanuka.